Muscle activation and performance during trunk strength testing in high-level female and male football players - Roth, R.; Donath, L.; Zahner, L.; Faude, O. (Journal of Applied Biomechanics, 2016)
For performance and injury prevention in sport, core strength and endurance are focused prerequisites. Therefore we evaluated characteristics of trunk muscle activation and performance during strength-endurance related trunk field tests. Strength-endurance ability, as total time to failure, and activation of trunk muscles was measured in 39 football players of the highest German female football league (Bundesliga) (N = 18, age: 20.7 y [SD 4.4]) and the highest national male under-19 league (N = 21, age: 17.9 y [0.7]) in prone plank, side plank, and dorsal position. Maximal isometric force was assessed during trunk extension and flexion, rotation, and lateral flexion to normalize EMG and to compare with the results of strength-endurance tests. For all positions of endurance strength tests, a continuous increase in normalized EMG activation was observed (P < .001). Muscle activation of the rectus abdominis and external oblique in prone plank position exceeded the maximal voluntary isometric contraction activation, with a significantly higher activation in females (P = .02). We conclude, that in the applied strength-endurance testing, the activation of trunk muscles was high, especially in females. As high trunk muscle activation can infer fatigue, limb strength can limit performance in prone and side plank position, particularly during high trunk muscle activation.